Generation of a transgene-free iPS cell line (SDQLCHi053-A) from a young girl carrying a heterozygous mutation (c.427C > T) in SYNGAP1 gene - Yanxin Wang; Xiaomeng Yang; Haiyan Zhang; Ning Liu; Yong Liu; Zhongtao Gai; Yi Liu; Yuqiang Lv (Stem Cell Research, 2023)
The pathogenic mutations of Synaptic Ras GTPase-activating protein 1 (SYNGAP1) gene (OMIM #603384) have been tightly associated with a neurodevelopmental disease, also called autosomal dominant mental retardation type 5 (MRD5, OMIM #612621). We generated a human iPS cell line from a 34-month-old young girl bearing a recurrent heterozygous mutation (c.427C > T) of SYNGAP1. This cell line has great performance in pluripotency and shows differentiation potential towards three germ layers in vitro.